Changes in free and bound fractions of aroma compounds of four Vitis vinifera cultivars at the last ripening stages - Vilanova, Mar (2012)
The volatile composition of white Agudelo, Blanco lexitimo, Godello and red Serradelo cultivars (NW Spain) harvested at two different stages of ripening have been evaluated. C6-compounds, alcohols, volatile fatty acids, monoterpenes, C13-norisoprenoids, volatile phenols and carbonyl compounds were identified and quantified in free and glycosidically bound forms by gas chromatography–mass spectrometry (GC–MS). The total volatile concentration showed a significant increase between the two ripening stages studied for all cultivars. The free volatile composition increased during maturity for Godello and Serradelo cultivars; however the glycosidically bound concentration increases for all cultivars with exception of B. lexitimo. Free C6-compounds ((E)-2-hexanal, 1-hexanol and (E)-2-hexen-1-ol) and bound alcohols (benzyl alcohol and 2-phenylethanol) showed the highest concentrations of volatile compounds for all grape cultivars in the two dates studied. Godello cultivar showed the highest change of volatile concentration between two ripening dates because of the high value of free C6-compounds. B. lexitimo was the most terpene-rich cultivar at the last ripening stage due to linalool; however C13-orisoprenoids in free form were detected in low concentrations for all cultivars but not in Godello and B. lexitimo cultivars at the last ripening stage. Free hexanoic acid increased during ripening in all cultivars. The evolution of volatiles during ripening of grape juice from the cultivars studied was not proportional to the changes in sugar content, which shows that the technological and aromatic maturities did not occur at the same time in these cultivars. The results also showed the cultivar ripening date interaction for all, free and bound, groups of compounds.